1985
DOI: 10.1159/000166941
|View full text |Cite
|
Sign up to set email alerts
|

Antiproteinuric Effect of Naproxen and Indomethacin

Abstract: In a double-blind crossover study in 10 salt-depleted nephrotic patients the reduction of proteinuria was significantly larger during indomethacin 50 mg three times daily than during naproxen 250 or 500 mg three times daily (72 vs. 44%, p < 0.05; 77 vs. 46%, p < 0.05, respectively). Both drugs induced similar reversible intrarenal hemodynamic changes, but indomethacin had more pronounced effects than naproxen. A common pathway, such as the reduction of the glomerular filtration rate and a reduction of the glom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…While this action has been noted previously by ourselves [7,8,13,14] and others [6,[9][10][11]15] with various NSAIDs. this is the first double-blind study against placebo to be reported.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…While this action has been noted previously by ourselves [7,8,13,14] and others [6,[9][10][11]15] with various NSAIDs. this is the first double-blind study against placebo to be reported.…”
Section: Discussionsupporting
confidence: 74%
“…For some authors, it is associated with a decrease in glomerular filtration [10], for others, the antiproteinuric effect and the effect on glomerular filtra tion are dissociated [15,16], A small decrease in filtra tion can be observed at the beginning of treatment. Fil tration however returns to normal in spite of continued treatment and when the antiproteinuric effect persists.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for this is derived from studies using nonsteroidal anti-inflammatory drugs (NSAIDs), which block the production of prostaglandins. Interestingly, proteinuria can be reduced by pharmacological treatments with NSAIDs both in experimental models of glomerular injury and in clinical practice (13,23,35,(37)(38)(39). The mechanism of action of NSAIDs in this context is currently unknown.…”
mentioning
confidence: 99%
“…First, it is clearly dependent on the dose of the drugs. For indomethacin, naproxen, and flurbiprofen, the maximal allowed chronic dose had to be used for achieving an optimal antiproteinuric effect (46,40). Second, not only the dose of the NSAID, but also the specific NSAID determined the degree of response.…”
Section: Antiproteinuric Properties Count: Another Strategy?mentioning
confidence: 99%